Determining the impact of timing and of clinical factors during end‐of‐life decision‐making in potential controlled donation after circulatory death donors. Issue 12 (26th August 2020) - Kotsopoulos, Angela M.; Jansen, Nichon E.; Vos, Piet; Witjes, Marloes; Volbeda, Meint; Epker, Jelle L.; Sonneveld, Hans P. C.; Simons, Koen S.; Bronkhorst, Ewald M.; van der Hoeven, Hans G.; Abdo, Wilson F.
Abstract : Controlled donation after circulatory death (cDCD) occurs after a decision to withdraw life‐sustaining treatment and subsequent family approach and approval for donation. We currently lack data on factors that impact the decision‐making process on withdraw life‐sustaining treatment and whether time from admission to family approach, influences family consent rates. Such insights could be important in improving the clinical practice of potential cDCD donors. In a prospective multicenter observational study, we evaluated the impact of timing and of the clinical factors during the end‐of‐life decision‐making process in potential cDCD donors. Characteristics and medication use of 409 potential cDCD donors admitted to the intensive care units (ICUs) were assessed. End‐of‐life decision‐making was made after a mean time of 97 hours after ICU admission and mostly during the day. Intracranial hemorrhage or ischemic stroke and a high APACHE IV score were associated with a short decision‐making process. Preserved brainstem reflexes, high Glasgow Coma Scale scores, or cerebral infections were associated with longer time to decision‐making. Our data also suggest that the organ donation request could be made shortly after the decision to stop active treatment and consent rates were not influenced by daytime or nighttime or by the duration of the ICU stay. Abstract : For potential donation after circulatory death donors, the authors assess the end‐of‐life decision‐making process from admission to the decision to withdraw life‐sustaining treatment and show that consent rates for organ donation are not associated with either intensive care unit stay duration or day‐ versus nighttime family approach.